Enhancement of electro-optic properties of nonlinear optical chromophores by introducing pentafluorobenzene group into the donor and π-bridge. (November 2019) - Lei, Jinlong; Guo, Chengjun; Liu, Fenggang; Chen, Shujie; Shi, Wen-Jing; Wang, Ziwei; Zhai, Zhaofen; Mo, Songmin; Wang, Jiahai
Abstract: Two isophorone-based chromophores A-B has been synthesized and investigated based on diethylaminophenyl donor and tricyanovinyldihydrofuran or phenyl-trifluoromethyltricyanofuran acceptors. The chromophores were modified with a bulky pentafluorobenzene group covalently attached to both the donor and bridge section of the chromophores to prevent close packing of molecules, which benefit the polarization efficiency. The ultraviolet absorption, Density functional theory (DFT) calculation, thermal stabilities and electro-optic activities of these chromophores were systematically studied. The chromophores A-B exhibited good thermal stabilities with the decomposition temperatures (Td ) higher than 220 °C. Most importantly, the rigid steric hindrance groups can effectively reduce intermolecular electrostatic interactions to translate the hyperpolarizabilities of chromophore into large electro-optic (EO) coefficients (r33 ). Polymers doped with 30 wt% chromophore A-B have been poled to afford ultrahigh electro-optic coefficient (r33 ) of 115 pm/V and 213 pm/V, respectively at 1.31 μm, which is higher than that of analogue chromophores which without isolation groups. Graphical abstract: Image 1 Highlights: Two chromophores A and B functionalized with pentafluorobenzene group had been synthesized. The decomposition temperatures of chromophores A and B are higher than 220 °C. The r33 value of film-A/PMMA and A/PMMA is 115 and 213 pm/V, respectively, at 1.31 μm.